The Aroids of the West Sarawak Limestone - Peter C., Boyce; Wong Sin, Yeng (International Aroid Society Inc., 2009)
The limestone (batu kapur in the local Bahasa Melayu) areas of Sarawak are among the most rewarding for searching for aroids, not only in terms of species richness but also species diversity. A particularly striking aspect of the limestone flora is that spatially close areas of limestone, often only a few kilometres distant, often have strikingly different species composition.